2015
DOI: 10.1007/s12663-015-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Prospective Study of Two Different Treatment Sequences i.e. Bottom Up–Inside Out and Topdown–Outside in, in the Treatment of Panfacial Fractures

Abstract: Within the limitation of low sample size we found that both bottom-up inside-out and top-down outside-in approaches have similar clinical outcomes. Hence it could be suggestive to start fixation of least disrupted (more stable) facial half as a guide for reconstruction of the remaining. Choice of the bottom-up inside-out or top-down outside-in sequence should be according to the pattern of fractures and preference of the surgeon. However, further controlled clinical trials, comparative studies with a larger sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 14 publications
0
21
0
3
Order By: Relevance
“…Numerous studies have compared combinations of these reduction sequences. However, the efficacy of inside-out or outside-in sequences have not been assessed independently of bottom-to-top or top-to-bottom sequences [ 4 5 6 7 9 ]. The “bottom-to-top and outside-in” approach is the most widely used method in the panfacial bone reduction [ 2 4 5 7 9 ].…”
Section: Various Sequences Of Panfacial Bone Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have compared combinations of these reduction sequences. However, the efficacy of inside-out or outside-in sequences have not been assessed independently of bottom-to-top or top-to-bottom sequences [ 4 5 6 7 9 ]. The “bottom-to-top and outside-in” approach is the most widely used method in the panfacial bone reduction [ 2 4 5 7 9 ].…”
Section: Various Sequences Of Panfacial Bone Reductionmentioning
confidence: 99%
“…Fractures of the frontal bone, maxilla, zygomatic complex, nasoethmoid-orbital (NEO) region, and mandible are the most common [ 1 2 3 ]. In simpler terms, panfacial bone fractures involve the midface and mandible [ 4 ]. Even experienced surgeons find restoration of the original facial architecture difficult because of the severe degree of fragmentation and the loss of all reference segments that could guide the start of facial reconstruction [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors recommend disimpaction and fixation of palatal fractures to use the maxillary dental arch as a template for the mandibular dental arch to maintain proper facial width. 21,25 To confirm proper reduction, normal bony landmarks and subtle cues from fracture alignment should be respected. During maxillomandibular fixation, preexisting dental wear facets can confirm proper occlusion.…”
Section: Facial Skeleton Managementmentioning
confidence: 99%
“…Degala et al prospectively compared two common treatment sequences with 11 patients total (6 in the "top-down" group and 5 in the "bottom-up" group) and found that all patients were able to obtain normal occlusion, and there was no statistically significant difference in mouth opening, facial symmetry, or overall treatment outcome between the two groups. 25 The ideal approach should be individualized. The senior authors use a combination of these approaches and start with less comminuted segments with more visible reference points to ensure proper reduction and avoid compounding error by fixation of subsequent more comminuted and difficult fracture segments.…”
Section: Facial Skeleton Managementmentioning
confidence: 99%